“Deadline” is Metaphorically Bad and Good: A Corpus-assisted Study on Indonesian Twitter Users’ View - Septiyatik, Dyta; Arimi, Sailal (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Deadline is an issue related to punctuality that highly seeks publics’ attention in their everyday life, especially for people in Indonesia who are known by their term of jam karet ‘always not being on time, describing as the stretches like rubber’. Coming up from the phenomenon, this study aims to reveal the metaphor of deadline expressed by Indonesians in Twitter. The data was collected using the hashtag feature of #deadline and filter feature on the first phase in gathering tweets related to deadline which were generated by Indonesian Twitter users. A group of tweets found through hashtag #deadline was subsequently analyzed using the concordance tool of AntConc to obtain the collocates and cluster, and was followed by Metaphor Identification Procedure (MIP) to determine the metaphorical expressions that brought about conceptual metaphor on deadline through domain mappings. The result of the study showed that Indonesian people make use of Twitter as a media to express their hustling days through hashtag metaphorically. The metaphorical expressions found were mapped to the source domain which reached to a conclusion that DEADLINE IS A TERROR. This outcome led to general idea that deadline was portrayed as something awful, threatening, and compulsive. Moreover, deadline is an embodiment of something full of adrenaline, challenging, and all rapid. The later portrayal resulted in a metaphor that DEADLINE IS A SURVIVAL GAME. In general, Indonesian Twitter users view deadline as a thrilling and unpredictable thing, either positively or negatively.